Simulation of extractive distillation for separating Acetonitrile-Toluene using Butyl Propionate as entrainer - Prasetyo, Dwi Agus; Han, Sang-Wook; Shin, Kyung-Jun; Kim, Byung-Jick (Jurnal Teknika, 2023)
Acetonitrile is known as a polar solvent that can dissolve in non-polar hydrocarbon liquids. As an example of a nonpolar solvent, toluene is one of the solvents that dissolves well in acetonitrile. If acetonitrile and toluene are mixed, a minimum boiling azeotrope will form. The maximum purity of acetonitrile when distilled is 89.5% mole at 81.19 °C under conventional distillation. To achieve high purity of acetonitrile, a new solvent should be added to this mixture. In this work, high purity of acetonitrile (99.9% mass) with extractive distillation method was simulated using Aspen Plus software. Based on the pseudo-binary analysis by Aspen Plus, butyl propionate can break the azeotrope mixture at concentration of 0.3 (mole fraction). The simulation results showed that, to get 99.9% mass of acetonitrile, a solvent to feed ratio of 1.5, reflux ratio of 1.5 a number of stages of 32 were required. After obtained the optimum parameters, economic evaluation was calculated using total annual cost (TAC) objective function method. From the economic evaluation, a feasible TAC of 1.225×106 $/year was obtained.